A 4-week internal training load monitoring and fatigue responses of malaysian under-18 rugby players during competitive season - Azis, Muhamad Fakhrul Hakim (2018)
Monitoring internal training loads using session ratings of perceived exertion (RPE) has been used extensively to manage fatigue and to optimise sports performance in athletes but none was reported in Malaysian athletes. Accurate monitoring of internal training loads could assist coaches in the adjustment of training, mode, intensity and duration during the competitive season. This study was to quantify the internal training loads (training load, monotony and strain) and fatigue and to identify the correlation of internal loads on fatigue responses of Malaysian under-18 rugby players for 4-weeks during competitive season. Thirty eight male participants of the study, aged from 16-18 years old, were recruited among the students from the Kolej Vokasional Pengkalan Chepa (N=38). The research variables of this study were collected in four weeks prior to their competition. After 90 minutes of every training session, they were asked to rate their training session using the RPE scale. Then, the Multidimensional Fatigue Symptom Inventory (MFSI)-Short form were administered once per week at the end of their training session for 4 weeks. The participants were trained five days per week as per coach’s training programme, hence the total number of days of data collection were 20 days. The types of training consisted of cardiovascular, strength, power and tactical. All data was entered into Microsoft Excel 2013. Statistical analyses was performed using IBM SPSS version 24.0. All data are presented as mean } standard deviation (SD) in descriptive statistics. The statistical analysis used in this study was repeated measure ANOVA. The statistical significance was set 0.05. Pearson correlation at p was used to analyse the relationship between internal training load variables and MFSI. Results showed that the training load in week 4 (2594.00 } 2.30) was significantly higher compared to week 1 (2388.55 } 343.87), week 2 (2284.34 } 411.41) and week 3 (2218.42 } 521.63). Monotony in week 4 was higher (1.70 } 3.13) compared to week 3 (1.43 } 0.44). The mean of monotony in week 2 was higher (1.60 } 0.35) than week 1 (1.49 } 0.09). Strain increased in week 2 was higher (3728.44 } 1228.51) compared to week 1 (3605.57 } 653.51). In week 3, the mean strain decreased (3354.59 } 1810.58) and increased in week 4 (4145.66 } 306.38). In training load, monotony, strain and the total score of fatigue (TSF) correlation, the result showed that training load increased with moderate correlations to TSF (r=0.342; r=0.402; r=0.469). In monotony (r=354; r=0.371; i=0.421) and strain (r=0.343; r=0.383; r=0.446), there were also moderate correlation to TSF. The results obtained in this study will help the coaches and trainers to develop an effective training programme in order to maximise their athlete’s performance, reduce fatigue and subsequently prevent injuries.